1998
DOI: 10.1007/s002590050312
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of metastatic melanoma utilising a technetium-99m labelled RGD-containing synthetic peptide

Abstract: Integrins are cell-surface glycoproteins found in different forms on all cells except erythrocytes. Integrins bind to cell adhesion molecules and to proteins found in the extracellular matrix. A tripeptidic sequence Arg-Gly-Asp (RGD) is often the primary site of recognition by integrins which are expressed on tumour cells and are responsible for tumour invasion and metastasis. A synthetic decapeptide designated alpha P2 containing two RGD sequences radiolabelled with technetium-99m was used to image malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 18 publications
1
54
0
5
Order By: Relevance
“…The results reported here describe how these tumors models have enabled us to verify the potential of 111 In-RGD 2 as a specific antiangiogenic marker in HNSCC, a feature that, despite much clinical and preclinical research into radiolabeled RGD peptides as a tracer for integrin a v b 3 (11,18,20,25,26), was still uncertain. SPECT/CT imaging showed clear uptake of the tracer in areas corresponding with vascularized areas of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reported here describe how these tumors models have enabled us to verify the potential of 111 In-RGD 2 as a specific antiangiogenic marker in HNSCC, a feature that, despite much clinical and preclinical research into radiolabeled RGD peptides as a tracer for integrin a v b 3 (11,18,20,25,26), was still uncertain. SPECT/CT imaging showed clear uptake of the tracer in areas corresponding with vascularized areas of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In micro-SPECT imaging studies, mice with FaDu, SCCNij3, or SCCNij202 tumor xenografts were injected intravenously with 1 mg of 111 In-RGD 2 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A 50-fold cold excess of RGD 2 was coinjected to investigate receptor-mediated localization of the radiolabeled peptide.…”
Section: Micro-spect/ctmentioning
confidence: 99%
“…99m Tc-αP2 99m Tc-αP2 is a peptide comprised of ten amino acids that contains two copies of the RGD motif for integrin-specific binding, and coupling to 99m Tc was accomplished over cysteine residues introduced into the peptide. 99m Tc-αP2 for imaging of integrin expression had been reported in 1988, even before integrin-specific PET tracers became available [60]. A clinical study in patients with malignant melanoma revealed a good detection rate of metastases in the neck, axilla, abdomen and soft tissue; however, sensitivity was reported to be low in the thorax due to high blood pool activity in the heart.…”
Section: Multimeric Compoundsmentioning
confidence: 96%
“…52 Since platelets are a major, biologically active constituent of a thrombus, there may be an advantage in using platelettargeted agents. 53 In the fast growing thrombus, platelets are activated. The activated platelets express the cellsurface integrin glycoprotein IIb/IIIa (GPIIb/IIIa) receptor which recognizes peptides containing the Arg-Gly-Asp (RGD) sequence, whereas non-activated circulating platelets express virtually none of the receptor in its active conformation.…”
Section: T H R O M B U S I M a G I N G P E P T I D E R A D I O P H mentioning
confidence: 99%